2017
DOI: 10.1038/cddis.2017.533
|View full text |Cite
|
Sign up to set email alerts
|

BAFF is involved in macrophage-induced bortezomib resistance in myeloma

Abstract: We aimed to characterize the role of B-cell activating factor (BAFF) in macrophage-mediated resistance of multiple myeloma (MM) cells to bortezomib (bort), and to further understand the molecular mechanisms involved in the process. First, we detected BAFF and its three receptors on myeloma cells and macrophages using the quantitative reverse transcriptase-polymerase chain reaction and flow cytometry. The secretion of BAFF was tested in patients with MM, MM cell lines, and macrophages. The ability of macrophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…The progressive effects of macrophages and fibroblasts on tumor growth are associated with the release of growth factors and anti-inflammatory mediators, their promotion of cancer invasiveness by releasing matrix degradation enzymes, and their involvement in the recruitment of suppressive cells, including T regulatory cells to the tumor side (31,32). Both aforementioned cell subsets have been shown to produce high levels of BAFF and APRIL; however, the effects of both ligands on the activation and biological function of tumor-infiltrating macrophages and tumor-associated fibroblasts remain elusive (18,24,(33)(34)(35). BAFF via direct interaction with TACI may therefore induce monocyte maturation towards macrophages and, thus, contribute to tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…The progressive effects of macrophages and fibroblasts on tumor growth are associated with the release of growth factors and anti-inflammatory mediators, their promotion of cancer invasiveness by releasing matrix degradation enzymes, and their involvement in the recruitment of suppressive cells, including T regulatory cells to the tumor side (31,32). Both aforementioned cell subsets have been shown to produce high levels of BAFF and APRIL; however, the effects of both ligands on the activation and biological function of tumor-infiltrating macrophages and tumor-associated fibroblasts remain elusive (18,24,(33)(34)(35). BAFF via direct interaction with TACI may therefore induce monocyte maturation towards macrophages and, thus, contribute to tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive new research has confirmed NF-κB signaling as critical in bortezomib resistance in MM cells ( 16 ). B-cell activating factor (BAFF), a cytokine in the TNF ligand family, is another important molecule shown to induce PI-resistance in MM cells ( 42 ). BAFF can drive macrophage-mediated PI-resistance and suppress caspase activation in MM cells through activation of Src, Erk1/2, Akt, and NF-κB signaling ( 42 ).…”
Section: Soluble Factor-mediated Drug Resistancementioning
confidence: 99%
“…B-cell activating factor (BAFF), a cytokine in the TNF ligand family, is another important molecule shown to induce PI-resistance in MM cells ( 42 ). BAFF can drive macrophage-mediated PI-resistance and suppress caspase activation in MM cells through activation of Src, Erk1/2, Akt, and NF-κB signaling ( 42 ). Recent work from Qin et al has shown that anti-BAFF-R antibody therapies had remarkable single-agent antitumor effects and induced potent antibody-dependent cellular cytotoxicity (ADCC) against multiple subtypes of human lymphoma and leukemia ( 16 ); we propose these may be useful in MM as well.…”
Section: Soluble Factor-mediated Drug Resistancementioning
confidence: 99%
“…MM-MΦs exhibit greater proliferation, resulting in elevated MM-MΦs levels in MM tumor bed 5 . Additionally, relative to regular MΦs, MM-MΦs confer MM cells with higher protection from chemotherapeutic agents 6 9 . Past studies indicate that MM-MΦs promote angiogenesis in MM BM 10 .…”
Section: Introductionmentioning
confidence: 99%